P187 Anal cancer and precursor lesions in HIV-infected persons: a clinical cohort study. (14th July 2019) - Ye, Yuanfan; Burkholder, Greer; Wiener, Howard; Mukherjee, Amrita; Gubbels, Alexandra; Shrestha, Sadeep
Abstract : Background: Infection with high-risk human papillomavirus increases the risk of developing anal cancer (AC). AC is rare in general populations (incidence rate: 1.8 cases per 100, 000 each year). However, recent studies have seen an increased number of AC among people living with HIV-1 infection (PLWH). We aimed to investigate AC regarding its incidence rate and sociodemographic characteristics in a HIV clinical cohort in the southeastern United States. Methods: Electronic health records between 2006 and early 2018 from an academic HIV Clinic at the University of Alabama at Birmingham were reviewed retrospectively. The HIV clinic treats more than 30% of total PLWH in Alabama. Patients with at least two clinical visits and aged 18 and above at HIV diagnoses were included. Age at AC diagnosis, self-reported race and sexual orientation were tested in univariate analyses. All significant variables were fitted in a multivariable logistic model adjusting for nadir CD4 counts and highest viral load (VL) prior to AC diagnoses or last clinical visits for non-AC subjects. Results: Among 4, 484 PLWH (1632 whites, 2676 blacks, 176 other races; 1031 women, 3429 men, 24 transgenders) over a total follow-up of 22188 years, there were 43 ACs (all men, 24 whites, and 18 blacks).The median age at AC diagnoses was 52; 36 were men who have sex with men (MSM) and 7 were heterosexual men (P<0.0001). The incidence was 267.2 cases per 100, 000 men each year. Being male (P<0.0001), MSM ( P <0.0001), white ( p =0.03), aged 45–54 years ( p =0.02), and with low nadir CD4 ( p <0.0001) were independently associated with AC. Conclusion: AC incidence among HIV-infected men was 148.4 times higher with earlier onset than general populations. However, public awareness of AC screening, specifically among the targeted population is lacking. This study can be valuable for the development of related screening programs and clinical practice guidelines for PLWH in the region. Disclosure: No significant relationships.